Towards decarbonization of shipping: direct emissions & life cycle impacts from a biofuel trial aboard an ocean-going dry bulk vessel. Issue 7 (12th January 2022) - Stathatou, Patritsia Maria; Bergeron, Scott; Fee, Christopher; Jeffrey, Paul; Triantafyllou, Michael; Gershenfeld, Neil
Abstract : Emissions from a dry bulk vessel operating on a biofuel blend were measured. Although marginal differences were observed in CO2 emissions from combustion compared to conventional marine fuels, life cycle CO2 emissions can be reduced by up to 40%. Abstract : On board emission measurements from a dry bulk vessel operating on an advanced biofuel, produced from used cooking oil (UCO), are reported for the first time, in an effort to assess potential benefits and impacts compared to conventional fossil fuels. Carbon dioxide (CO2 ) and nitrogen oxide (NO x ) emission measurements were performed on a slow-speed, two-stroke marine diesel engine of a Kamsarmax vessel, while burning a 50 : 50 biofuel blend of UCO biodiesel and marine gas oil (MGO). The same gases were monitored, under similar conditions, while the vessel was burning solely low-sulfur MGO (LSMGO) allowing for relevant comparisons. Sulfur dioxide (SO2 ) emissions were also calculated for the tested fuels. Apart from comparing the biofuel blend with LSMGO in terms of direct emissions from combustion, indirect emissions associated with the extraction, production and transportation of both fuels were estimated based on recent literature. Life cycle emissions were also estimated for different scenarios involving conventional marine fuels for performing the same voyage. Marginal differences were observed regarding CO2 and NO x emissions of the tested fuels, while the SO2 emissions of the biofuel blend were about 50% lower compared to LSMGO. Although the biofuel blend generates combustion CO2 emissions very similar to those of conventional marine fuels, it can achieve up to 40% emissions reduction from a life cycle analysis (LCA) perspective. These results, combined with the fact that no operational issues occurred during the biofuel trial, show that such fuels have significant potential towards the decarbonization of dry bulk shipping.